Research in Industrial Marketing: Issues and Opportunities Classification - Qurtubi, Qurtubi; Kusrini, Elisa (International Journal of Integrated Engineering, 2019)
This article discusses about researches on industrial marketing. It is designated to provide more understanding correlated with researches conducted in industrial marketing. Literature reviews are expected to provide support to researchers in performing future researches. Literature review is employed for this article. Based on the result and discussion, it can be concluded that the researches on industrial marketing were grouped into nine topics, which are: the differences between business-to-business (B2B) marketing and business-to-consumer (B2C) marketing, theory and practices in industrial marketing, marketing-selling interface, purchasing and supply management, customer relationship management (CRM), industrial marketing strategy, correlation between industrial marketing and information technology, business-to-business (B2B) digital marketing, as well as correlation between business-to-business- (B2B) marketing and social media. Therefore, the most preferable topics to be studied are theory and industrial marketing practices.